Validating the Strategic Deployment of Blackleg Resistance Gene Groups in Commercial Canola Fields on the Canadian Prairies - Cornelsen, Justine; Zou, Zhongwei; Huang, Shuanglong; Parks, Paula; Lange, Ralph; Peng, Gary; Fernando, W. G. Dilantha (Frontiers in Plant Science, 2021)
Blackleg, caused by the fungal pathogen Leptosphaeria maculans, is a serious threat to canola (Brassica napus L.) production in western Canada. Crop scouting and extended crop rotation, along with the use of effective genetic resistance, have been key management practices available to mitigate the impact of the disease. In recent years, new pathogen races have reduced the effectiveness of some of the resistant cultivars deployed. Strategic deployment and rotation of major resistance (R) genes in cultivars has been used in France and Australia to help increase the longevity of blackleg resistance. Canada also introduced a grouping system in 2017 to identify blackleg R genes in canola cultivars. The main objective of this study was to examine and validate the concept of R gene deployment through monitoring the avirulence (Avr) profile of L. maculans population and disease levels in commercial canola fields within the Canadian prairies. Blackleg disease incidence and severity was collected from 146 cultivars from 53 sites across Manitoba, Saskatchewan, and Alberta in 2018 and 2019, and the results varied significantly between gene groups, which is likely influenced by the pathogen population. Isolates collected from spring and fall stubble residues were examined for the presence of Avr alleles AvrLm1, AvrLm2, AvrLm3, AvrLm4, AvrLm5, AvrLm6, AvrLm7, AvrLm9, AvrLm10, AvrLm11, AvrLepR1, AvrLepR2, AvrLep3, and AvrLmS using a set of differential host genotypes carrying known resistance genes or PCR based markers. The Simpson’s evenness index was very low, due to two dominant L. maculans races (AvrLm2-4-5-6-7-10-11 and AvrLm2-5-6-7-10-11) in representing 49% of the population, but diversity of the population was high from the 35 L. maculans races isolated in Manitoba. AvrLm6 and AvrLm11 were found in all 254 L. maculans isolates collected in Manitoba. Knowledge of the blackleg disease levels in relation to the R genes deployed, along with the L. maculans Avr profile helps to measure the effectiveness of genetic resistance.